Metabolomics mechanism of traditional soy sauce associated with fermentation time - Li Zhu; Siyu He; Ying Lu; Jianhong Gan; Ningping Tao; Xichang Wang; Zaoli Jiang; Yuanxiang Hong; Changhua Xu (Food Science and Human Wellness)
Given that fermentation time has significant impact on quality and flavor of soy sauce, a global understanding of the metabolic mechanism as fermentation time prolonged is essential for producing satisfactory and consistent quality of traditional soy sauce. Herein, the metabolic compounds changes of soy sauce associated with fermentation time up to 10 years were comprehensively investigated by using Chinese traditional fermented soy sauce (CTFSS) as a demonstration. Results showed that formaldehyde nitrogen, total soluble nitrogen (TSN), non-salt soluble solids, amino acids, free 5’-nucleotides and volatile compounds in CTFSS changed obviously during fermentation. Specifically, glutamic acid and aspartic acid were prominent in CTFSS. Continuous decrease in content of hypoxanthine (Hx) was found from 1 M (1-month soy sauce) to 7 M (7-months soy sauce). Furthermore, a significant opposite tendency for changes between some volatile compounds and amino acids was indicated that there was a transformation between these two components. Therefore, a better understanding to the influence of fermentation time on soy sauce had been proposed. As the formation and conversion of amino acids and sugars might be mainly responsible for flavor formation in CTFSS, the ratio of these two reactions rate led the metabolism to be divided into three steps, degradation, conversion and balance.